Survival of antibiotic resistant bacteria following artificial solar radiation of secondary wastewater effluent - Glady-Croue, J.; Niu, X.; Ramsay, Joshua; Watkin, E.; Murphy, R.; Croue, Jean-Philippe (Elsevier, 2018)
Urban wastewater treatment plant effluents represent one of the major emission sources of antibiotic-resistant bacteria (ARB) in natural aquatic environments. In this study, the effect of artificial solar radiation on total culturable heterotrophic bacteria and ARB (including amoxicillin-resistant, ciprofloxacin-resistant, rifampicin-resistant, sulfamethoxazole-resist ant, and tetracycline-resistant bacteria) present in secondary effluent was investigated. Artificial solar radiation was effective in inactivating the majority of environmental bacteria, however, the proportion of strains with ciprofloxacin-resistance and rifampicin-resistance increased in the surviving populations. Isolates of Pseudomonas putida, Serratia marcescens, and Stenotrophomonas maltophilia nosocomial pathogens were identified as resistant to solar radiation and to at least three antibiotics. Draft genome sequencing and typing revealed isolates carrying multiple resistance genes; where S. maltophilia (resistant to all studied antibiotics) sequence type was similar to strains isolated in blood infections. Results from this study confirm that solar radiation reduces total bacterial load in secondary effluent, but may indirectly increase the relative abundance of ARB.